Program for Infection and Cancer Prevention Activities (PROACTIVE) towards knowledge and attitudes of self-hygiene and breast self-examination for adolescents - Fithriyyah, Yayu Nidaul; Rachmawati, Meyka Budi; Farhany, Fajrul Falah; Nugroho, Nur Huda Adi (Journal of Community Empowerment for Health, 2025)
Introduction: Pesantren are Islamic educational institutions that implement a boarding system. Insufficient sanitation increases the risk of contagious disease transmission. Besides infectious diseases. Moreover, there is a rising trend of cancer incidence in adolescents.Objective: To evaluate the effectiveness of the Program for Infection and Cancer Prevention Activities (PROACTIVE) on knowledge and attitudes regarding personal hygiene, infectious diseases, and cancer among students in the Pesantren.Methods: This study used a quasi-experimental design with a single-group pre-test and post-test approach. It was conducted at MA Nur Iman Sleman, located within a Pesantren environment, 47 students completed both the pre- and post-test questionnaire. Data were analyzed using descriptive and inferential statistics.Results: The study at MA Nur Iman revealed a significant increase in knowledge about Acute Respiratory Infections (ARIs) post-intervention, especially in Class 1 (from 2.91 to 3.07, P=0.0001). Scores related to personal hygiene, handwashing, residential cleanliness, and women's reproductive health showed good scores. However, the overall practice of Breast Self-Examination (BSE) did not show significant changes, However, two statements related to laziness and embarrassment during BSE showed significant improvements (P=0.000).Conclusions: The intervention was effective in enhancing awareness and attitudes regarding Acute Respiratory Infections (ARIs). However, there is a need for an engaging and continuous educational approach to form a lasting awareness and attitude among adolescents, particularly concerning cancer.